Is 2(–2) + 6(2) equivalent to (–3)(–3) + (–1)(1)?

Let negative numbers be represented with a "–" symbol and positive numbers be represented by "+" symbol.

Use a pictorial model to justify your answer.

2(–2) + 6(2)= -4+12=8

(–3)(–3) + (–1)(1)= 9-1=8

the answer is yes

best me please

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up